ALT+F: PENGEMBANGAN FITUR REKOMENDASI LAPANGAN FUTSAL TERDEKAT DIANTARA DUA TIM BERBASIS ANDROID MENGGUNAKAN ALGORITMA DIJKSTRA - Muhaqiqin, Muhaqiqin; Rikendry, Rikendry (J-Icon : Jurnal Komputer dan Informatika, 2023)
The development of futsal is rapid and is the fastest-growing sport in indoor sports worldwide. Playing futsal has become a lifestyle, especially for people in large cities. Futsal not only has become a lifestyle but also has different levels of play, ranging from amateur to semi-professional and professional. The level of play can be seen through competitions organized by Fédération Internationale de Football Association (FIFA) and futsal organizations in each country. Futsal competitions require thorough preparation, even at the amateur level. The playing experience of futsal players needs to be enhanced, so teams need different opponents. There are challenges in finding other teams to play against, such as teams not being familiar with each other, which means teams have to wait for competitions or futsal tournaments. In addition, the lack of information about the nearest futsal court location between teams that want to compete is also a challenge, making it difficult for teams to invite opponents for practice matches. Therefore, a platform is needed to find practice match opponents that includes a feature recommending the nearest futsal court between the two teams. In this research, a feature recommending the nearest futsal court between two teams is developed by implementing the Dijkstra algorithm. The development of this feature in the application uses the software development method called design sprint, which focuses on user needs, ensuring that the application's features align with user expectations. As a result, the application can display recommendations for the nearest futsal court between two teams that want to practice matches. This makes it easier for teams to determine the closest venue that is easily accessible for both teams and their opponents.